Fundamentals of high-frequency CMOS analog integrated circuits - Leblebici, Duran (Cambridge University Press, 2009)
With a design-centric approach, this textbook bridges the gap between fundamental analog electronic circuit textbooks and more advanced RF IC design texts. The major issues that must be taken into account when combining analog and digital circuit building blocks are covered, together with the key criteria and parameters that are used to describe system-level performance. Simple circuit models enable a robust understanding of high-frequency design fundamentals, and SPICE simulations are used to check results and fine-tune the design. With solved design examples to guide the reader through the decision process that accompanies each design task, this is an ideal textbook for senior undergraduate and graduate courses in RF CMOS circuits, RF circuit design, and high-frequency analog circuit design. Analog integrated circuit designers and RF circuit designers in industry who need help making design choices will also find this a practical and valuable reference.